PLAY-BASED AND MULTI-SENSORY LEARNING APPROACHES IN TASKA: MEETING THE NEEDS OF INFANTS, TODDLERS, AND PARENTS - AINUL SOFEEYA SHUKRAN; MOHD NAZRI ABDUL RAHMAN (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
This study explores the teaching and learning approaches used for infants and toddlers in Taman Asuhan Kanak-kanak (TASKA) and how these practices align with parents’ aspirations for early education. A qualitative approach was used, involving a semi-structured interview with one TASKA teacher responsible for children aged two months to four years. The findings show that play-based, multi-sensory, and routine-integrated activities are the main strategies that promote children’s holistic development, especially in language, social, and motor skills. Parents generally prioritise safety, health, and early growth, while some focus more on academic readiness. This difference creates challenges for teachers in balancing developmental needs with academic expectations. The study concludes that maintaining developmentally appropriate practices, improving communication with parents, and providing regular teacher training, adequate resources, and clear management support are essential to enhance the quality of teaching and align TASKA practices with parents’ expectations.